Path planning and intelligent control of a soft robot arm based on gas-structure coupling actuators - Xu, Yan; Li, Hongwei; Li, Hua; Fang, Guanhui; Jia, He (Frontiers in Materials, 2022)
A fully 3D-printed soft pneumatic robotic arm based on two types of gas-structure coupling actuators is designed for on-orbit servicing. The path planning algorithm and trajectory tracking intelligent control strategy of the arm are developed. A model-free closed-loop control system with a PID controller and an iterative learning controller is built to improve the performance speed for repeated tasks. An experiential knowledge database for an iterative learning controller is described. The effectiveness of the iterative learning controller is verified by comparative experiments. The obstacle avoidance path planning algorithm based on the A* algorithm is presented. The validity of the path planning algorithm and trajectory tracking control strategy are verified by obstacle avoidance path planning experiments. The experimental results show that intelligent motion control and obstacle avoidance of the fully 3D-printed soft robotic arms are realized within an acceptable error.